Determinants of Bowel Preparation Quality and Its Association With Adenoma Detection: A Prospective Colonoscopy Study. Issue 2 (January 2016) - Wong, Martin C.S.; Ching, Jessica Y.L.; Chan, Victor C.W.; Lam, Thomas Y.T.; Luk, Arthur K.C.; Tang, Raymond S.Y.; Wong, Sunny H.; Ng, Siew C.; Ng, Simon S.M.; Wu, Justin C.Y.; Chan, Francis K.L.; Sung, Joseph J.Y.
Abstract : Abstract: The predictors of poor bowel preparation in colorectal cancer screening participants have not been adequately studied, and the association between the quality of bowel preparation and adenoma detection has not been firmly established. This study examined the determinants of poor bowel preparation, and evaluated its relationship with adenoma detection. We included subjects aged between 50 and 70 years who received colonoscopy between 2008 and 2014 in a colorectal cancer screening program in Hong Kong. The quality of the bowel preparation was assessed by colonoscopists, and the factors associated with poor bowel cleansing were evaluated by a binary logistic regression analysis. A multivariate regression model was constructed to evaluate if poor bowel preparation was associated with detection of colorectal neoplasia. From 5470 screening participants (average age 57.7 years, SD 4.9), 1891 (34.6%) had poor or fair bowel preparation. The average cecal intubation time was 7.0 minutes (SD 5.4; range 1.22–36.9 minutes) and the average colonoscopy withdrawal time was 10.8 minutes (SD 6.9; range 6.0–107.0 minutes). Among all, 26.5% had colorectal neoplasia and 5.5% had advanced neoplasia. Older age (≥60 years; adjusted odds ratio [AOR] = 1.19–1.38, P  = 0.02–0.04), male sex (AOR = 1.38, 95% confidence interval [CI] 1.19–1.60, P  < 0.001), and current smoking (AOR = 1.41, 95% CI 1.14–1.75, P  = 0.002) were significantly associated with poor/fair bowel preparation. Poorer cleansing resulted in significantly lower detection rate of neoplasia (AOR = 0.35–0.62) and advanced neoplasia (AOR = 0.36–0.50) irrespective of polyp size. Steps to improve proper procedures of bowel preparation are warranted, especially among subjects at risk of poor bowel preparation. Strategies should be implemented to improve bowel cleansing, which is now demonstrated as a definite quality indicator.